2000
DOI: 10.1177/002194360003700305
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, Corporate Strategy, and Cul tural Context: What Is the Mission for International Business Communication?

Abstract: A global economy requires business organizations to cultivate their international holdings by respecting the national differences of their host countries and coordinating efforts for rapid innovation. In this essay we first review relevant literature in the areas of communication and innovation and explore how efforts toward innovative practices are directly related to globalism and business strategy. We then focus on issues associated with national culture, corporate culture, and professional culture that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 51 publications
1
25
0
3
Order By: Relevance
“…Ulijn and his colleagues [22][23][24][25] have argued that professional communicators often play a crucial role in formulating strategic innovation targets of companies and helping them implement and assess this formulation process with guidelines suitable for the company's culture. They then use the various functions of the strategic targets with different professional cultures, such as engineering and marketing, and act as crosspollinators in exchanging ideas and information between top, middle, and lower management.…”
Section: An Innovation Perspectivementioning
confidence: 99%
“…Ulijn and his colleagues [22][23][24][25] have argued that professional communicators often play a crucial role in formulating strategic innovation targets of companies and helping them implement and assess this formulation process with guidelines suitable for the company's culture. They then use the various functions of the strategic targets with different professional cultures, such as engineering and marketing, and act as crosspollinators in exchanging ideas and information between top, middle, and lower management.…”
Section: An Innovation Perspectivementioning
confidence: 99%
“…For example Higgins (1996) found that U.S. and European executives display a more positive attitude toward open, specific and timely communications than their Japanese counterparts. But strong differences also are present within low contextcultures: Ulijn et al (2000) showed that readers from French and Dutch business letters (when both translated into English) recognized substantial differences in structure and were likely to prefer the letters that were originally written in their mother tongue.…”
Section: Financial Versus Non-financial Disclosurementioning
confidence: 99%
“…Using a somewhat varied approach, Ulijn et al (2000) employed a psycholinguistics to study the dissemination of scientific and technical innovations across linguistic borders. In short, each of these studies tends to view communication as a tool to diffuse organizational innovation.…”
Section: Current Views On the Diffusion Of Innovation In Organizationsmentioning
confidence: 99%